2019
DOI: 10.1002/jwmg.21737
|View full text |Cite
|
Sign up to set email alerts
|

Diets of native and introduced tree squirrels in Washington

Abstract: Competition for food resources can be a primary mechanism for displacement of native species by introduced species. Investigation of dietary partitioning between potential competitors and spatiotemporal variability in food resources can reveal contested food items and intensity of competition. Introduced eastern gray squirrels (Sciurus carolinensis) have been implicated as competitors with western gray squirrels (S. griseus) and Douglas’ squirrels (Tamiasciurus douglasii), but little is known about interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Nevertheless, it was apparent that western gray squirrels do not require riparian areas to support populations in our study area. As in California (Byrne 1979), western gray squirrels on the Base, but not eastern gray squirrels, frequently foraged on seeds of conifers; however, both species consumed truffles with similar frequency in our study area (Johnston et al 2019). Many riparian areas on the Base had dense shrub cover, which was a top predictor for discriminating habitats of eastern and western gray squirrels in analyses of vegetation at field plots (Johnston 2013).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Nevertheless, it was apparent that western gray squirrels do not require riparian areas to support populations in our study area. As in California (Byrne 1979), western gray squirrels on the Base, but not eastern gray squirrels, frequently foraged on seeds of conifers; however, both species consumed truffles with similar frequency in our study area (Johnston et al 2019). Many riparian areas on the Base had dense shrub cover, which was a top predictor for discriminating habitats of eastern and western gray squirrels in analyses of vegetation at field plots (Johnston 2013).…”
Section: Discussionmentioning
confidence: 49%
“…Eastern gray squirrels may be poorly adapted to conifer‐dominated forests with little diversity of deciduous trees and shrubs. Douglas‐fir and ponderosa pine were the dominant conifers on much of our study area, but we rarely observed eastern gray squirrels feeding on their seeds (Johnston et al 2019). In their native range, eastern gray squirrels often use bottomland hardwood forests and avoid uplands dominated by conifers (Fischer and Holler 1991, Riege 1991, Steele and Koprowski 2001).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations